Influence of TiO2 Nanocrystals Fabricating Dye-Sensitized Solar Cell on the Absorption Spectra of N719 Sensitizer. (8th July 2012) - Wen, Puhong; Han, Yinfeng; Zhao, Weixing
Abstract : The absorption spectra of N719 sensitizer anchored on the films prepared by TiO2 nanocrystals with different morphology and size were investigated for improving the performance of dye-sensitized solar cell (DSC). We find that the morphology and size of TiO2 nanocrystals can affect the UV-vis and FT-IR spectra of the sensitizer anchored on their surfaces. In particular, the low-energy metal-to-ligand charge-transfer transitions (MLCT) band in the visible absorption spectra of N719 is strongly affected, and locations of these MLCT bands revealed larger differences. The results indicate that there is a red shift of MLCT band in the spectra obtained by using TiO2 nanocrystals with long morphology and large size compared to that in solution. And it produced a larger red-shift on the MLCT band after TiO2 nanocrystals with small size mixed with some long nanocrystals. Accordingly, the utilization rate to visible light is increased. This is a reason why the DSC prepared by using such film as a photoelectrode has better performance than before mixing.